2020
DOI: 10.1097/cm9.0000000000000642
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of different doses of pioglitazone in psoriasis: a meta-analysis of randomized controlled trials

Abstract: Background: Pioglitazone may be beneficial in the treatment of psoriasis. However, based on the effectiveness and safety considerations, it has not been widely used. To fully evaluate the strength of evidence supporting psoriasis treatment with pioglitazone, we conducted a meta-analysis of existing published studies. Methods: PubMed, Ovid, Cochrane Library, Google Scholar, and Web of Science databases were systematically searched before February 2019. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…One of most common AGIs, acarbose, augmented colonic butyrate production through the upregulation of butyrate‐producing bacteria in vitro, 36 but the F/B ratio was not significantly affected with acarbose use in the mouse model 4 . Treatment with metformin, liraglutide, anagliptin, vildagliptin and dapagliflozin in a mouse model led to a decreased F/B ratio, 4 and the results are consistent with recent studies that have shown that psoriasis incidence in patients with DM may be reduced by the use of hypoglycaemic drugs, such as biguanides, TZDs and GLP‐1 receptor agonist; however, the effect of DPP‐4 inhibitors and dapagliflozin are controversial, it needs to further investigation in a human study 18‐22,37‐42 . In addition to gut microbiota, the treatment mechanism of DM and relative complications may be towards inflammation reduction induced by hypoglycaemic agents 43 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One of most common AGIs, acarbose, augmented colonic butyrate production through the upregulation of butyrate‐producing bacteria in vitro, 36 but the F/B ratio was not significantly affected with acarbose use in the mouse model 4 . Treatment with metformin, liraglutide, anagliptin, vildagliptin and dapagliflozin in a mouse model led to a decreased F/B ratio, 4 and the results are consistent with recent studies that have shown that psoriasis incidence in patients with DM may be reduced by the use of hypoglycaemic drugs, such as biguanides, TZDs and GLP‐1 receptor agonist; however, the effect of DPP‐4 inhibitors and dapagliflozin are controversial, it needs to further investigation in a human study 18‐22,37‐42 . In addition to gut microbiota, the treatment mechanism of DM and relative complications may be towards inflammation reduction induced by hypoglycaemic agents 43 .…”
Section: Discussionsupporting
confidence: 88%
“…4 Treatment with metformin, liraglutide, anagliptin, vildagliptin and dapagliflozin in a mouse model led to a decreased F/B ratio, 4 and the results are consistent with recent studies that have shown that psoriasis incidence in patients with DM may be reduced by the use of hypoglycaemic drugs, such as biguanides, TZDs and GLP-1 receptor agonist; however, the effect of DPP-4 inhibitors and dapagliflozin are controversial, it needs to further investigation in a human study. [18][19][20][21][22][37][38][39][40][41][42] In addition to gut microbiota, the treatment mechanism of DM and relative complications may be towards inflammation reduction induced by hypoglycaemic agents. 43 Chen et al indicated that acarbose decreased rheumatoid arthritis risk in patients with diabetes through a potential immunomodulatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Serious adverse effects including hypoglycemic events were not reported in any studies included in meta-analyses. 8,9 Pioglitazone also improved metabolic parameters in patients with psoriasis. 10…”
Section: Thiazolidinediones (Tzd)mentioning
confidence: 98%
“…As for the different doses of pioglitazone in psoriasis, the daily 30 mg dose was significantly related to a greater therapeutic effect than that of the 15 mg dose per day with no significant change in the frequency of adverse reactions. This means that the amelioration from pioglitazone in psoriasis is dose-dependent[ 4 , 12 ].…”
Section: Antidiabetic Drugs On Psoriasismentioning
confidence: 99%